Pengembangan Media Pembelajaran Matematika Dalam Materi Bangun Datar di Sekolah Dasar Menggunakan Model ADDIE Berbasis Kearifan Lokal Masyarakat Baduy - Agustian, Gogi; Arisetyawan, Andika (Universitas Pendidikan Indonesia Kampus Serang, 2022)
Mathematics is one of the subjects found at every level of education from elementary school to high school and even college. However, it’s often heard that mathematics is one of the subjects that most students are uninterested in, of course there are many things behind this case. This is in line with the discovery of researchers in the field who are majoring in education. After making several observations in various schools, the researchers found several things that caused this to happen, among others the low interest of students in learning mathematics from the beginning, students’ difficulties in understanding the lesson material and students’ lack of enthusiasm for learning. Researchers realize that there are differences in students’ interests and abilities in mathematics lessons, but researchers are interested in students who actually have an interest in mathematics but are less enthusiastic in participating in learning. After going through various interviews, researchers found several reasons why students were less enthusiastic in participating in mathematics learning activities in class. Including class situations and boring learning processes, too much lesson material that was delivered by the teacher, and the delivery of lesson material that was difficult to understand by students. The research conducted aims to overcome the problems encountered by developing learning media so that it is expected to increase students’ enthusiasm in participating in mathematics learning. The selected learning media is a popular board game called monopoly that is modified in such a way as needed with reference to using the ADDIE model and integrating the media with local culture that is local wisdom of the Baduy society.